2017
DOI: 10.1007/s11368-017-1899-6
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis and critical evaluation of influencing factors on soil carbon priming following biochar amendment

Abstract: Purpose Previous studies have found biochar-induced effects on native soil organic carbon (NSOC) decomposition, with a range of positive, negative and no priming reported. However, many uncertainties still exist regarding which parameters drive the amplitude and the direction of the biochar priming. Materials and methods We conducted a quantitative analysis of 1170 groups of data from 27 incubation studies using boosted regression trees (BRTs). BRT is a machine learning method combining regression trees and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 71 publications
3
51
0
Order By: Relevance
“…While mechanisms responsible for the accumulation of biogenic soil organic C in the biochar‐amended plots are not yet fully understood, we suggest, based on literature, that time after biochar application, soil textural class, soil water content, biochar pyrolysis temperature, and quality and quantity of initial soil C are potential factors affecting priming (Ding et al, ; Maestrini et al, ; Wang et al, ). For instance, the negative priming effect can increase with an increase in soil water content, biochar pyrolysis temperature, and soil clay content (Ding et al, ). A review of 21 studies, although mostly laboratory studies, concluded that biochar retarded the mineralization of soil organic matter by 3.8% in fine‐textured soils, but it accelerated mineralization of soil organic matter by 20.8% in sandy and low‐fertility soils (Wang et al, ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…While mechanisms responsible for the accumulation of biogenic soil organic C in the biochar‐amended plots are not yet fully understood, we suggest, based on literature, that time after biochar application, soil textural class, soil water content, biochar pyrolysis temperature, and quality and quantity of initial soil C are potential factors affecting priming (Ding et al, ; Maestrini et al, ; Wang et al, ). For instance, the negative priming effect can increase with an increase in soil water content, biochar pyrolysis temperature, and soil clay content (Ding et al, ). A review of 21 studies, although mostly laboratory studies, concluded that biochar retarded the mineralization of soil organic matter by 3.8% in fine‐textured soils, but it accelerated mineralization of soil organic matter by 20.8% in sandy and low‐fertility soils (Wang et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Water content at −33 kPa (cm 3 /cm 3 ) quantity of initial soil C are potential factors affecting priming (Ding et al, 2018;Maestrini et al, 2015;Wang et al, 2016). For instance, the negative priming effect can increase with an increase in soil water content, biochar pyrolysis temperature, and soil clay content (Ding et al, 2018).…”
Section: Mean Weight Diameter Of Water-stable Aggregates (Mm)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Although the term "priming" (14) is widely-used to describe this phenomenon, due to broad interpretations of the term (15), we will refer to "increased or decreased mineralization"; even though less concise, this method-and process-agnostic term will help ensure clarity and avoid prior expectations of what the term "priming" implies.) Research over the past decade has progressed beyond observation of the phenomenon to systematic investigations of the mechanisms underlying these interactions (16)(17)(18), while the conclusions from meta-analyses have strengthened as the total number of studies of PyOM-SOC interactions has steadily increased (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, current understanding of mechanisms underlying interactive effects of PyOM additions on SOC mineralization includes the following observations (19)(20)(21)(22): (1) In general, when changes in mineralization do occur, net increases in nSOC mineralization tend to be limited to the earlier stages of incubations or field studies, while net decreases in nSOC mineralization often emerge later. (2) It is essential to consider the specific properties of PyOM and the soil to which it is applied together.…”
Section: Introductionmentioning
confidence: 99%